EXPLORING THE ENGLISH WORD FORMATION PROCESS (A Literature Review) - Dirgeyasa, I Wayan (Journal of Language, Literature and Teaching, 2024)
It is a fact that word formation is a crucial aspect of linguistics, particularly the morphology study. Its importance can help us learn new words, understand how languages change, and improve our communication skills in real interaction and communication among others. Like other sciences, language science or linguistics, specifically the morphology which is known as the study of word formation developed rapidly and massively due to the rapid development of science and technology. As a result, the vocabulary of any language is constantly changing, adding new words and phrases. This, of course enriches the vocabulary and words of the language itself. This article deals with the nature of word formation process and types of the word formation in the study of the language, particularly the English language. Key words: word formation, concept, type, and English